Penataan Penguasaan Tanah Di Kawasan Perbatasan Negara - Hadi Arnowo (Jurnal Transformasi Administrasi, 2018)
Indonesian Land Border with neighbor state countries is based on Regulation Number 43 on 2008 about The Territory of the State is with Malaysia, Papua New Guinea and Timor Leste. The purpose of writing on the land mastery arrangement is to know the concrete steps related to the arrangement of land mastery in border area and spatial arrangement correlation with arrangement of land tenure. The physical condition of the border area is generally wavy to hilly. Land use in the border area consists of forests, farms and settlements. The status of land in the border area is generally divided into state-controlled free land, state-occupied land, property and ulayat lands. Arrangement of land tenure in general includes maintaining existing land status, granting of rights to land, disposal of rights and adjustment of land rights. The designation of border area according to the prevailing regulations is divided into areas of defense, cultivation area and conservation area. Arrangement of land tenure stipulated by the spatial is to refer to the function of the area. Development of border areas by strengthening land rights will provide legal certainty of land rights so as to provide a sense of security in investing and land use.